Feasibility study of electric vehicles (EVs) in Singapore using HOMER Grid - Chen, Benedict Fu Shen (Nanyang Technological University, 2024)
EVs have become the centrepiece of sustainable urban mobility worldwide. This is because they are powered by electricity and have zero tailpipe emissions. However, contention on the sustainability of EVs is on the rise. Some argue that its sustainability depends on the source of energy derivation for charging EV batteries. Hence, energy required to charge EVs should be from sustainable renewable sources (i.e., solar panels, wind turbines, hydro dams, etc).